Receptor Oligomerization in Family B1 of G-Protein-Coupled Receptors: Focus on BRET Investigations and the Link between GPCR Oligomerization and Binding Cooperativity - Roed, Sarah N.; Orgaard, Anne; Jorgensen, Rasmus; De Meyts, Pierre (Frontiers in Endocrinology, 2012)
The superfamily of the seven transmembrane G-protein-coupled receptors (7TM/GPCRs) is the largest family of membrane-associated receptors. GPCRs are involved in the pathophysiology of numerous human diseases, and they constitute an estimated 30-40 % of all drug targets. During the last two decades, GPCR oligomerization has been extensively studied using methods like bioluminescence resonance energy transfer (BRET) and today, receptor-receptor interactions within the GPCR superfamily is a well-established phenomenon. Evidence of the impact of GPCR oligomerization on e.g. ligand binding, receptor expression, and signal transduction indicates the physiological and pharmacological importance of these receptor interactions. In contrast to the larger and more thoroughly studied GPCR subfamilies A and C, the B1 subfamily is small and comprises only 15 members, including e.g. the secretin receptor (SECR), the glucagon receptor (GCGR), and the receptors for parathyroid hormone (PTHR1 and PTHR2). The dysregulation of several family B1 receptors is involved in diseases, such as diabetes, chronic inflammation, and osteoporosis which underlines the pathophysiological importance of this GPCR subfamily. In spite of this, investigation of family B1 receptor oligomerization and especially its pharmacological importance is still at an early stage. Even though GPCR oligomerization is a well-established phenomenon, there is a need for more investigations providing a direct link between these interactions and receptor functionality in family B1 GPCRs. One example of the functional effects of GPCR oligomerization is the facilitation of allosterism including cooperativity in ligand binding to GPCRs. Here, we review the currently available data on family B1 GPCR homo- and heteromerization, mainly based on BRET investigations. Furthermore, we cover the functional influence of oligomerization on ligand binding as well as the link between oligomerization and binding cooperativity.